2014
DOI: 10.1509/jim.14.0065
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Technology Acceptance Model under Different Cultural Contexts: The Case of Online Shopping Adoption

Abstract: Global usage of the Internet has increased remarkably in the past few decades, thus necessitating a better understanding of e-commerce adoption across cultures. Against this backdrop, this study contributes to the existing technology adoption and acceptance literature in the following ways. First, the authors develop an extended technology acceptance model that incorporates trust and perceived behavioral control and examine it in settings outside the United States to better understand the adoption of e-commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
202
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 97 publications
(191 reference statements)
16
202
1
9
Order By: Relevance
“…From a technology acceptance perspective, studies have shown that individual beliefs-PU and PEOU-mediate the effect of external factors on individuals' attitudes towards and intention to purchase from a website (Ashraf et al, 2014;Chen et al, 2002;Venkatesh and Davis, 2000). As illustrated in Figure 1, and in line with the regulatory fit and technology acceptance literatures, we expect that in addition to being more engaged, individuals experiencing fit will not only perceive the website as easier to use, but will also perceive it as more useful.…”
Section: Regulatory Fit and Underlying Mechanisms (Engagement Pu Anmentioning
confidence: 59%
See 2 more Smart Citations
“…From a technology acceptance perspective, studies have shown that individual beliefs-PU and PEOU-mediate the effect of external factors on individuals' attitudes towards and intention to purchase from a website (Ashraf et al, 2014;Chen et al, 2002;Venkatesh and Davis, 2000). As illustrated in Figure 1, and in line with the regulatory fit and technology acceptance literatures, we expect that in addition to being more engaged, individuals experiencing fit will not only perceive the website as easier to use, but will also perceive it as more useful.…”
Section: Regulatory Fit and Underlying Mechanisms (Engagement Pu Anmentioning
confidence: 59%
“…Engagement has been shown to mediate fit effects; however, a review of regulatory fit and technology acceptance literature reveals that engagement may not be the only factor that mediates the effect of fit (Wang and Lee, 2006;Lee at al., 2010;Ashraf et al, 2014;Venkatesh and Davis, 2000). Drawing on the regulatory fit and technology acceptance literatures, our study identifies other mechanisms that clarify how regulatory focus exerts its effects.…”
Section: Regulatory Fit and Underlying Mechanisms (Engagement Pu Anmentioning
confidence: 96%
See 1 more Smart Citation
“…Nell'industria dell'ospitalità, internet assume, in effetti, un ruolo sempre maggiore in virtù della crescente propensione, da parte dei viaggiatori, a ricercare informazioni e realizzare prenotazioni online (Ashraf et al, 2014;Sabiote-Ortiz et al, 2016;Sia et al, 2009;Straub et al, 1997). È interessante notare come i viaggiatori provenienti da contesti individualisti, nonostante siano più indipendenti ed autonomi nelle proprie scelte, ripongono molta importanza nelle recensioni online che vengono utilizzate per elaborare un proprio giudizio sulle potenziali strutture da visitare.…”
Section: Lo Sviluppo Delle Analisi Cross-cultural Il Modello DI Hofsunclassified
“…Una meta-analisi dell'effetto moderatore della cultura sui processi di acquisto online ha rilevato, inoltre, l'importanza dell'utilità percepita come fattore determinante delle scelte di acquisto dei consumatori occidentali (culture prevalentemente individualiste) e non dei consumatori asiatici (culture collettivistiche) (Zhang et al, 2012). Ashraf et al (2014) e Straub et al (1997) hanno analizzato, invece, il ruolo dell'uncertainty avoidance, riscontrando che i consumatori provenienti da paesi ad elevato rifiuto dell'incertezza tendono ad acquistare meno online, ma ripongono molta fiducia nelle recensioni, che leggono con estrema attenzione.…”
Section: Lo Sviluppo Delle Analisi Cross-cultural Il Modello DI Hofsunclassified